The Effect of Discipline, Communication, and Training During Work from Home on Employee Performance at PT. Nusantara III Plantation Medan - Angelina Malau; Cut Fitri Rostina; Magdalena Br Sianturi; Kesita Togatorop (Journal of Research in Business, Economics, and Education, 2022)
This study aims to examine and analyze the effect of discipline, communication, training during work from home on employee performance at PT Perkebunan Nusantara III Medan. Employee performance at PT. Perkebunan Nusantara III is a problem in completing its work because the WFH carried out by this company makes all performance limited and results in a decrease in employee performance. As a result, employees at the company find it difficult to carry out the tasks given, it is difficult to control employee activities and is still lacking in data reporting. On discipline, where discipline in the company decreases due to WFH so that employees in the company are late for absences, do other work during working hours, and lack of compliance with regulations. In communication, where communication within the company is lacking due to limited communication resulting in lack of coordination between superiors and subordinates, lack of attention from employees when listening to directions, decreased concentration at work, lack of tools such as those in the office. In this company training is lacking during WFH so that employees find it difficult to achieve targets, difficult to do tasks, and lack of understanding of tasks resulting in employees working below standard and ineffective. This study uses quantitative research with the sample used is 87 people. The data analysis method used multiple linear regression. Simple random sampling was used as a sampling method. In the t-test on the discipline variable with a value of (4,554 > 1,988), communication (3,285 > 1,988) and training (3,920 > 1,988) partially positive and significant effect on employee performance at PT Perkebunan Nusantara III Medan. In the F test, the variables of discipline, communication and training showed a positive and significant effect with a value (189.240>2.71) on employee performance at PT Perkebunan Nusantara III Medan.